Prevalence Of Dengue In Patients Presenting To A Tertiary Care Hospital Of Karachi - Gul Ahuja; Saba Shahnawaz; Sumera Sheikh; Adnan Zubairi; Kanaan Mansoor; Shanawer Khawaja; Zeerak Ahmed; Fatima Habib (ziauddin University, 2024)
Background: Dengue is a mosquito borne disease with worldwide distribution which has become endemic in certain regions of Pakistan and has given rise to a few epidemics. Infection with the Dengue virus can manifest itself as a severe, non-fatal viral syndrome or a rapidly progressive and a commonly fatal hemorrhagic fever. This study was conducted to investigate the prevalence of Dengue fever in the urban region of Karachi, Pakistan. Methods: This retrospective, cross-sectional study was conducted at the Ziauddin Hospital System comprising of three hospitals catering to various socio- economic strata of the society. 823 samples were collected from the hematology and microbiology department of the hospital and the Dengue NS 1 antigen ELISA test was performed. Patients of all age and both genders were included. Results: 823 patients were included in this study, out of which 32.1% (264) were found to have sera positive for Dengue IgM. Division according to sex demonstrated a predominance of males at 70.8% (n=177) while affected females accounted for 29.2% (n= 77). The most susceptible age group was found to be 30-39 years of age. Conclusion: The inhabitants of Karachi face a high probability of contracting this disease due to the unsanitary living conditions and lack of basic amenities .This study has shown the prevalence of Dengue to be higher in Karachi than in other cities of Pakistan, therefore effectual methods of prevention and control are the need of the hour. Key Words: Dengue fever, prevalence, NS1 antigen, Pakistan